Developing material-dialogic space in geography learning and teaching: Combining a dialogic pedagogy with the use of a microblogging tool. (March 2019) - Cook, V.; Warwick, P.; Vrikki, M.; Major, L.; Wegerif, R.
Highlights: A microblogging tool can be an 'active agent' in a dialogic classroom pedagogy. Material-dialogic space is a space of creative possibility. The enactment of provisionality supported exploratory talk. Dialogic switching aides the learning of the 'threshold' concept of sustainability. Abstract: Dialogic accounts of learning and teaching are not good at including the role of technology. In this exploratory study we use a material-discursive theoretical frame, initially derived from Barad, to apply the concepts of intra-action and affordance in explaining the contribution of the digital to classroom-based group tasks. The microblogging tool 'Talkwall' is the focus of this study. The aim of this study is to explore how dialogic intra-actions may develop in material-dialogic space, demonstrating how various affordances are enacted in response to task demands and consequent dialogue. This paper focuses on data from one geography lesson involving 29 students. It reports findings from a detailed micro analysis of intra-action of video data and lesson transcripts, comprising six Talkwall episodes. Through this analysis the concept of affordance is critiqued and we illustrate the intra-action possibilities that may facilitate the creative co-construction of ideas in the material-dialogic space created by the use of Talkwall. The significance of this paper lies in offering and illustrating a new approach to analysing learning and teaching where technology plays an important role.